KOMUNIKASI EDUKATIF DALAM PROSES PEMBELAJARAN - Hendri Fauza (Hijri, 2017)
Communications in the process of education is very important between teachers and students. Communication is conducted in order to be able to convey the instruction in learning so learner can run effectively and efficiently. Effectiveness and efficiency communication can be achieved if communication happen is an educative communication. To do in educative communication, teachers should have a good interpersonal competency. Communications should be viewed as a fundamental element and an integrated process of education which aim to facilitate the exchanging of messages, an idea or concept that result in the attractiveness of sender with accepter message, in the implementation of the school's education, so all the members need communication skill so much to do their task at school.